Presentation of Green Open Space of Makassar City inN WebGIS: Penyajian Ruang Terbuka Hijau Kota Makassar dalam WebGIS (JURNAL GEOCELEBES, 2023)
Green open space has three basic functions, among others, to function socially, namely as a facility for the public with the functions of recreation, education and sports, as well as establishing communication between city residents; to function physically, namely as the lungs of the city, protecting the water system, soundproofing, fulfilling visual needs, restraining the development of built-up land/as a buffer, and protecting city residents from air pollution; and functions as an aesthetic that is a binder between building elements in the city, a giver of characteristics in shaping the face of the city, and an element in the arrangement of urban architecture. Law No. 26 of 2007 concerning Spatial Planning, it is explained that the spatial planning of the city area must include a plan for the provision and utilization of green open space which covers at least 30% of the city area consisting of 20% public green open space and 10% consisting of private green open space. . But in reality, there are still many big cities that are not difficult to achieve the provisions of the law. This research will identify green open space in Makassar City by utilizing satellite image data and then presenting the green open space in the form of spatial information into a Web GIS so that it can be easily accessed openly. Based on the results of the analysis, the percentage of open green space in Makassar reached 9.08%, consisting of private green open space of 4.07% and public green open space of 5.01%.